Green supply chain management in the shipping industry - Alexandrou, Stelios (Department of Commerce, Finance and Shipping, Faculty of Management and Economics, Cyprus University of Technology, 2018)
The thesis provides a detailed empirical examination on GSCM in the context of the shipping industry, by conducting three innovative empirical studies: (i) resources and capabilities as drivers of proactive GSCM strategy, based on the NRBV theory, and resulting performance and competitive advantage implications, (ii) proactive GSCM strategy implementation and its relationship to financial performance, and (iii) the moderating effect of managerial propensity for risk-taking on the relationship between proactive GSCM strategy and performance. In chapter two, building on the natural resource-based view (NRBV) theory, I develop a model that examines the drivers of proactive green supply chain management (GSCM) strategy. We then examine the outcome of such strategy on the performance and competitive advantage of shipping firms. I collect data from a global sample of 289 shipping firms, including private and listed companies, and we apply structural equation modelling (SEM) to test the research hypotheses. Resources and capabilities emerge as drivers of GSCM strategy. Furthermore, I find support to the thesis that proactive GSCM strategy affects the environmental and economic performance of shipping firms positively, which in turn enhances competitive advantage. The associations revealed in this study can improve environmental management decisions and provide fruitful managerial and theoretical implications. In chapter three, this thesis empirically examines the relationship between levels of GSCM strategy adoption and the financial performance of shipping firms. I apply cluster analysis and analysis of variance (ANOVA), to test the research hypotheses. This study is able to cluster shipping firms according to their level of adoption of GSCM strategy, ranging from reactive to more proactive shipping companies. Furthermore, the study shows that shipping firms with a proactive GSCM strategy can achieve better financial performance. The findings of this thesis can improve the environmental management strategy decisions of shipping firms and support the elimination of environmental problems, while improving the financial performance of shipping firms. Chapter four investigates the moderating role of managerial propensity towards risk on the relationship between proactive GSCM strategy and environmental and economic performance. The study applies structural equation modelling (SEM) to test the research hypotheses. Results show that proactive GSCM strategy is beneficial to both the environmental and economic performance of shipping firms. The positive effects of a proactive GSCM strategy on environmental performance are stronger when managers are highly risk averse, while their level of risk aversion has no moderating effect on shipping firms’ economic performance.Several practical and managerial implications are discussed in this thesis that can assist shipping firms to enhance their performance and competitiveness. This thesis also identifies and discusses the limitations of each study and proposes ideas for future research.
Keywords: GSCM; Shipping industry; natural resource-based view (NRBV) theory; Green supply chain management (GSCM) strategy; Structural equation modelling (SEM)